Youth and Adults' Education in times of pandemic: what students and managers from Goiás say - Luciene Lima de Assis Pires; Paulo Henrique de Souza; Rosimary Batista da Silva; Alexsandra Pereira Silva de Souza (Universidade Federal do Oeste da Bahia, 2021)
This article presents reflections about the educational process in Youth and Adults Education (EJA). Using face-to-face and telephone semi-structured interviews, and through the monitoring of students' difficulties, it was sought to understand the reality of EJA subjects and their expectations about the school in times of pandemic. It's reported how remote classes were held and the view of managers and students on the teaching and learning process. In 2020/1, ten students were monitored in the disciplines of Science and Math, in five cities in Goiás. It's shown here part of the research: the follow up of two students: one in Biology and the other in Math, in two cities in Goiás. It was found that the two cities have different economic realities, but they are similar regarding to EJA during the pandemic. The increase in school dropout was noticed and it was found that the students had difficulties in attending the remote classes.